Copulatory efficiency and fertility in male rats exposed perinatally to flutamide - Leonelli, Carina [UNESP]; Garcia, Patricia C. [UNESP]; Pereira, Oduvaldo C. M. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
This study investigated the effects of perinatal treatment with flutamide on male sexual behavior, semen parameters, and fertility in adult male rats. Pregnant rats received 15 mg/kg of flutamide or peanut oil, s.c., at days 19 and 22 of pregnancy and for the first five postnatal days. Treated male offspring showed increases in latency to copulatory behavior, number of mounts without penis intromission, number of intromissions until ejaculation, latency to ejaculation, and reduced number of ejaculations. Flutamide treated rats presented reductions in weight of testes and prostate, percentage of normal spermatozoa, spermatozoa concentration, testicular sperm production, and testosterone level. Normal females mated with treated males presented more pre-implantation losses, reduced implantation rates, and consequently reduced offspring size. The results indicated that perinatal flutamide treatment damaged organizational processes of sexual differentiation, which led to inefficiency in copulatory behavior and reductions in sperm quality and count, resulting in low capacity for producing descendants. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Flutamide; Perinatal androgen blockade; Sexual behavior; Fertility; Sperm quality; Sperm count; Male rat